Technique For Image De-blurring Using Adaptive Wavelet Lagrange Fuzzy Filter - Sabeeh, A. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A new de-blurring technique was proposed in order to reduced or remove the blur in the images. The proposed filter was designed from the Lagrange interpolation calculation with adjusted by fuzzy rules and supported by wavelet decomposing technique. The proposed Wavelet Lagrange Fuzzy filter gives good results for fully and partially blurring region in images.